2017
DOI: 10.12775/cjfa.2016.022
|View full text |Cite
|
Sign up to set email alerts
|

Disclosing Non-Financial Information in Companies’ Reports in Croatia

Abstract: Subsequent to the provision of the Directive 2014/95/EU requiring disclosure of non-financial and diversity information of all EU Member States companies with 500 and more employees, a research was conducted at the beginning of 2016 on a sample of sustainability reports disclosed by Croatian companies in 2014 that had registered 400 and more employees in that same year, with an assumption of their growth by 2018 in terms of the number of their employees. This research was focused on the structure of the indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Persic and Halmi [19] studied the manner in which Croatian companies with at least 400 employees reported information according to the Directive. The data showed that many of the disclosed sustainability indicators are "story-tellers", meaning that they are past-oriented and qualitatively stated.…”
Section: Introductionmentioning
confidence: 99%
“…Persic and Halmi [19] studied the manner in which Croatian companies with at least 400 employees reported information according to the Directive. The data showed that many of the disclosed sustainability indicators are "story-tellers", meaning that they are past-oriented and qualitatively stated.…”
Section: Introductionmentioning
confidence: 99%
“…Reliability, completeness, consistency, comparability and connectivity are important qualitative characteristics of the information (IR 2016, 20) which should be followed in the process of preparing the destination's integrated report. Integrated reporting should also be focused on demonstrating a compliance of the achieved results with legal and other requirements and health tourism development strategic goals, defined in the framework of relevant national and regional strategic documents, as well as achieved level of practice development (Peršić 2012;Peršić and Janković 2012;Peršić and Janković 2014;Peršić, Vlašić and Janković 2016;Peršić and Halmi 2016;Peršić and Vlašić 2017).…”
Section: Figure 1: Economic Effects Of Providing Various Health-tourimentioning
confidence: 99%
“…The recent rise of stakeholder demand for non-financial reporting is one of the most pronounced consequences of the growing emphasis on social and ecological aspects of business operation as such (Stępień, 2015, p. 19). Professional literature provides a broad overview of problems related to disclosure of social and environmental information by business organisations (Krasodomska, 2017;Gabrusewicz, 2010;Samelak, 2013;Mazurczak, 2012;Fijałkowska, 2013;Peršić & Halmi, 2016;Haller, van Staden & Landis, 2016;Haller, Link & Gross, 2017). However, certain gaps can be identified in the evaluation of non-financial reporting by large financial institutions, particularly those in the banking segment of the economy.…”
Section: Reporting Of the Social And Environmental Responsibilitylitementioning
confidence: 99%